Strategi Pemasaran Ekonomi Kreatif pada Subsektor Kuliner dalam Meningkatkan Daya Saing UMKM - Hairul; Jauhari Maulana; Aprian Michella Stevania Riahayu; Muhyiddin Irfan Hafidz; Nandha Narendra Muvano (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The culinary subsector is a key pillar of the creative economy in Indonesia, contributing significantly to the growth of MSMEs. However, high levels of competition require culinary MSMEs to implement creative and adaptive marketing strategies to increase their competitiveness. This study aims to analyze creative economy marketing strategies in the culinary subsector to enhance MSME competitiveness through a Systematic Literature Review (SLR) approach. The research method involved searching and selecting relevant scientific articles from various academic databases, then analyzing them thematically to identify patterns, trends, and key findings related to creative economy culinary marketing. The study results indicate that creative economy-based marketing strategies, such as utilizing social media, product innovation, strengthening branding, storytelling, and emphasizing local values ​​and wisdom, play a critical role in enhancing the competitiveness of culinary MSMEs. Furthermore, digital technology support, increased marketing literacy, and collaboration between stakeholders are also contributing factors to the success of these marketing strategies. However, several challenges remain, including limited resources, low product standardization, and a lack of ongoing mentoring. This study concludes that implementing creative, integrated, and sustainable marketing strategies is key to strengthening the competitiveness of culinary MSMEs in the creative economy ecosystem.